(untitled) (Mother Language, 2026)
This study investigates the impact of the COVID-19 pandemic on the English language skills of tertiary-level students in Dhaka, Bangladesh, who shifted to online education. It focuses on the emergence of learning gaps in English proficiency due to the pandemic and the effects of online education on four essential language skills (speaking, writing, reading, and listening). Using a mixed-methods design, survey data from 36 students were complemented by interviews with three English language teachers. The results indicate significant declines in speaking and writing proficiency, attributed to reduced interaction, limited feedback, and technological barriers. Listening and reading were also affected, though to a lesser extent, due to poor audio quality, reduced concentration, and limited access to resources. Both teachers and students perceived online learning as considerably less effective than face-to-face instruction, with engagement, motivation, and confidence undermined by stress and unequal access to digital infrastructure. These findings highlight the vulnerability of productive language skills to emergency remote teaching and the impact of socioeconomic disparities on outcomes. The study emphasizes the importance of blended learning models, targeted teacher training in digital pedagogy, and improved infrastructure support to enhance post-pandemic English language education in Bangladesh Mother Language, 2025; 9 (2): 82-113